Agro-Tourism Service Enhancement in N akhon Pathom Province, Thailand: on Capability Increasing of the Hospitality of Agriculturists - Setthachotsombut, Natpatsaya; Aunyawong, Wissawa (International Journal of Supply Chain Management, 2020)
This research aims to study the knowledge used for Hospitality of Agriculturists for Agro-tourism (HAAT) and Tourism Service Enhancement (TSE), to create a hospitality model for agriculturists in Nakhon Pathom province, Thailand, and to study the effect of using the model on TSE. A mixed method was the research methodology. The data was collected from 800 samples selected from the population of 920,030 people in Nakhon Pathom province to ensure the data reliability and accuracy in the Structural Equation Modeling (SEM). The results found that 1) The Hospitality of Agriculturists for Agro Tourism (HAAT) has a positive direct effect on Tourism Service Enhancement (TSE), with the highest TSE in Word of Mouth/Repeat Travel (WM/RT),  2) Hospitality with Service Mind (HSM) has a positive direct and indirect effects on HAAT, and has a positive direct effect on TSE and Physical Hospitality (PH), and 3) HP has a positive indirect effect on HAAT, but has a positive direct effect on TSE and HSM. The agriculturists can use these findings for tourist hospitality with the same standard to improve the services so as to support in Impression Increase (II), Word of Mouth, and Revenue Increase (RI). It will help agriculturists to have a better life aside from relying only on income from the sale of agricultural products.